Hubungan Dukungan Suami Dengan Kejadian Unmet Need Kb Pada Pasangan Usia Subur (Pus) Di Wilayah Kerja Uptd Puskesmas Botania Kota Batam Pada Tahun 2024 - Asti Melinda Sapitri; Desiernita Amru; Nurfitri Nurfitri (Economics and Digital Business Review, 2024)
Unmet Need for KB is an unmet contraceptive need in fertile couples who do not want to have children or do not want to have children anymore but without implementing contraceptive methods, including pregnant women and unplanned pregnancies. The problem of family planning services in Indonesia one of them is the high number of Unmet Need for KB cases, which is 11%, higher than the national target of 7.40%. Husband's support is an important guideline for wives in making family planning decisions. The purpose of this study was to determine the relationship between husband's support and the incidence of unmet need for KB in fertile couples (PUS) in the Working Area of ​​the Botania Health Center UPTD, Batam City. This type of research is quantitative with a cross-sectional study design. The sample in this study was determined using a cluster random sampling technique of 99 fertile couples in the working area of ​​the Botania Health Center UPTD in 2024. The results of the chi-square analysis at a significance level of 95% showed that there was a relationship between husband's support and the incidence of unmet need for family planning in fertile couples in the Working Area of ​​the Botania Health Center UPTD, Batam City, which was indicated by a p-value of 0.003 (α <0.05). Efforts that midwives can make are promotional activities regarding contraceptive methods for both husbands and wives. Increasing husbands' knowledge and support about contraception is expected to increase the participation of couples of childbearing age in family planning programs.